The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1038/s41598-024-53756-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Th1-related cytokines and complicated pediatric appendicitis

Matilda Elliver,
Martin Salö,
Bodil Roth
et al.

Abstract: The pathogenesis of appendicitis is not understood fully, and the diagnosis can be challenging. Previous research has suggested an association between a T helper (Th) 1-dependent immune response and complicated appendicitis. This prospective cohort study aimed to evaluate the association between serum concentrations of the Th1-associated cytokines interleukin (IL)-1α, IL-1β, IL-2, IL-6, IL-10, IL-17A and tumor necrosis factor beta (TNF-β) and the risk of complicated appendicitis in children. Appendicitis sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The diagnostic value of IL-6 and its capacity to indicate the extent of appendicitis has been evaluated [ 24 ]. Systematic reviews and studies revealed a possible elevation of IL-6 levels in children with complicated appendicitis [ 25 , 26 ]. A prospective observational study was performed to verify the diagnostic role of IL-6 in distinguishing between uncomplicated and complicated pediatric appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic value of IL-6 and its capacity to indicate the extent of appendicitis has been evaluated [ 24 ]. Systematic reviews and studies revealed a possible elevation of IL-6 levels in children with complicated appendicitis [ 25 , 26 ]. A prospective observational study was performed to verify the diagnostic role of IL-6 in distinguishing between uncomplicated and complicated pediatric appendicitis.…”
Section: Discussionmentioning
confidence: 99%